Aversive gustatory learning and perception in honey bees - Guiraud, Marie (Sci Rep, 2018)
Taste perception allows discriminating edible from non-edible items and is crucial for survival. In the honey bee, the gustatory sense has remained largely unexplored, as tastants have been traditionally used as reinforcements rather than as stimuli to be learned and discriminated. Here we provide the first characterization of antennal gustatory perception in this insect using a novel conditioning protocol in which tastants are dissociated from their traditional food-reinforcement role to be learned as predictors of punishment. We found that bees have a limited gustatory repertoire via their antennae: they discriminate between broad gustatory modalities but not within modalities, and are unable to differentiate bitter substances from water. Coupling gustatory conditioning with blockade of aminergic pathways in the bee brain revealed that these pathways are not restricted to encode reinforcements but may also encode conditioned stimuli. Our results reveal unknown aspects of honey bee gustation, and bring new elements for comparative analyses of gustatory perception in animals.